Resilience in Emerging Adulthood Viewed from Social Support - Lekatompessy, Shella Kristiani; Dimala, Cempaka Putrie; Wulandari, Christina R (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
At each stage of development, individuals have tasks and demands that must be met during the transition from adolescence to adulthood. Term Emerging adulthood introduced by Arnett (2000), namely the phase of self-exploration in various aspects during the transition from adolescence to adulthood. To overcome obstacles and challenges in the future emerging adulthood, individuals must have the strength to endure and develop positive emotions. This ability is referred to as resilience. Resilience is an individual's ability to survive and adapt to difficult circumstances in their life. In order for the transition to be successful in facing change, individuals need social support to reduce psychological pressure and control negative emotions. StudyThis aims to determine the impact of social support on resilience in emerging adulthood in Karawang. This quantitative research involved 100 early adults in Karawang using a purposive sampling technique. Data collection was carried out using questionnaires distributed randomly.daring. Resilience is measured using the Connor-Davidson scaleResilience Scale (CD-RISC) modified by Yu & Zhang (2007), while social support was measured using scala Multidimensional Scale Perceived Social Support (MSPSS) from Zimet (2015) theory. The significance value shows that social support has a significant positive influence of (F=13.615) with sig. 0.000 (p<0.05), proving that there is a significant positive influence between social support on resilience in emerging adulthood in Karawang. The analysis results prove the coefficient of determination (R2) of 0.491, which means that social support has an influence of 49.1 percent, the remaining 50.9 percent is influenced by other factors outside the scope of this research. It is hoped that individuals who are in the future emerging adulthood, not to hesitate to ask for physical and psychological support from the surrounding environment in facing a developmental crisis.Di setiap tahap perkembangan, individu mempunyai tugas serta tuntutan yang harus terpenuhi di masa transisi dari remaja menuju dewasa. Istilah emerging adulthood dikenalkan oleh Arnett (2000), yaitu fase mengekplorasi diri dalam berbagai aspek di masa peralihan dari remaja menuju dewasa. Untuk mengatasi hambatan dan tantangan di masa emerging adulthood, individu harus memiliki kekuatan untuk bertahan dan mengembangkan emosi positif. Kemampuan ini disebut sebagai resiliensi. Resiliensi adalah kemampuan individu untuk bertahan dan beradaptasi pada keadaan sulit dalam hidupnya. Agar arahtransisi sukses dalam menghadapi perubahan, individu memerlukan dukungan sosial untuk menurunkan tekanan psikologis dan mengontrol emosi negatif. Penelitian ini bertujuan untuk mengetahui dampak dukungan sosial terhadap resiliensi pada emerging adulthood di Karawang. Penelitian kuantitatif ini melibatkan 100 dewasa awal di Karawang memakai teknik purposive sampling.Pengumpulan data dilakukan menggunakan penyebaran kuesioner secara daring. Resiliensi diukur menggunakan skala Connor-Davidson Resilience Scale (CD-RISC) yang dimodifikasi oleh Yu & Zhang (2007), sedangkan dukungan sosial diukur memakai skala Multidimensional Scale Perceived Social Support (MSPSS) dari teori Zimet (2015). Nilai signifikasi menunjukkan bahwa dukungan sosial memiliki pengaruh positif dengan signifikan sebesar (F=13,615) dengan sig. 0.000 (p< 0,05), membuktikan bahwa adanya pengaruh positif yang signifikan antara dukungan sosial terhadap resiliensi pada emerging adulthood di Karawang. Hasil analisis membuktikan nilai koefisiensi determinasi (R2) sebesar 0.491 yang berarti bahwa dukungan sosial memiliki pengaruh 49,1 persen, selebihnya sebesar 50,9 persen dipengaruhi faktor lain diluar cakupan penelitian ini. Diharapkan individu yang berada di masa emerging adulthood, untuk tidak ragu meminta dukungan secara fisik dan psikologis dari lingkungan sekitar dalam menghadapi krisis perkembangan.